Partial and Comprehensive Understanding: An Analysis of the Interpretation of the Ḥadīṡ of Riddah Punishment - Nabih Zaky Al-Fikri, M.; Musyafiq, Ahmad; Rochmawati, Nikmah (UIN Syarif Hidayatullah Jakarta, 2025)
Ḥadīṡ regarding the punishment of riddah is often debated because partial understandings tend to cause misunderstandings, such as the view that Islam does not provide freedom of religion. A partial understanding of the ḥadīṡ of riddah punishment is often considered contrary to the values of Islamic justice and creates a negative perception of Islamic teachings in modern society. This study aims to analyze the difference between partial and comprehensive approaches in understanding the ḥadīṡ about riddah punishment. Using a qualitative method based on library research, this study examines primary and secondary literature through a descriptive-analytical approach. The study results show that the partial approach tends to ignore other related ḥadīṡ, socio-historical contexts, and maqāsid asy-syarī’ah principles, resulting in rigid interpretations. Instead, a comprehensive approach emphasizes the importance of understanding ḥadīṡ in the context of maqāsid asy-syarī’ah, such as maintaining societal stability and religious freedom. This study recommends using a comprehensive approach to understanding the ḥadīṡ considered controversial, so their interpretation is more relevant to the principles of justice and humanity in Islam, especially in the modern era that upholds the value of freedom.